A Longitudinal Study of Glucose Tolerance in Cystic Fibrosis: The Central Role of Beta Cell Functional Mass - Piona, Claudia; Mozzillo, Enza; Tosco, Antonella; Zusi, Chiara; Emiliani, Federica; Volpi, Sonia; Di Candia, Francesca; Raia, Valeria; Boselli, Maria Linda; Trombetta, Maddalena; Cipolli, Marco; Bonadonna, Riccardo C; et al. (The journal of clinical endocrinology and metabolism, 2025)
The pathophysiological mechanisms underlying the natural history of glucose intolerance and its fluctuations in subjects with cystic fibrosis (CF) are still unclear. To investigate the relationship between longitudinal changes in glucose tolerance and concomitant changes in the main parameters of insulin secretion/metabolism/action determining glucose regulation in subjects with CF. Insulin sensitivity and glucose-stimulated insulin secretion (GSIS, a biomarker of beta cell functional mass), as estimated by the Oral Glucose Sensitivity Index (OGIS) and by a sophisticated mathematical model, respectively, and insulin clearance were assessed in 127 subjects with CF, aged 10-25 years, who underwent 2 oral glucose tolerance tests over an at least 1-year follow-up period. Subjects were classified a posteriori as regressors (improved glucose tolerance), stable, or progressors (worsened glucose tolerance). The interplay between beta cell compensatory action and insulin sensitivity over time was analyzed by vector plots of insulin clearance adjusted GSIS (PCadj) vs OGIS. OGIS decreased in progressors and stable. Insulin clearance decreased in both regressors and progressors. GSIS (beta cell functional mass) improved in regressors and worsened in progressors, whereas it did not change in stable. Vector plot analysis confirmed that glucose regulation changed differently in each group. Multinomial logistic regression analysis showed that baseline glucose tolerance and GSIS changes were the only significant predictors of the changes in glucose tolerance (P < .02, R2 Nagelkerke = 0.55), whereas age, gender, z body mass index, CF genotypes, and baseline adjusted proportional control were not. In subjects with CF, changes in beta cell functional mass are associated with favorable or detrimental changes of glucose tolerance over time.